2022
DOI: 10.1007/jhep01(2022)106
|View full text |Cite
|
Sign up to set email alerts
|

Production of light (anti)nuclei in pp collisions at $$ \sqrt{s} $$ = 13 TeV

Abstract: Understanding the production mechanism of light (anti)nuclei is one of the key challenges of nuclear physics and has important consequences for astrophysics, since it provides an input for indirect dark-matter searches in space. In this paper, the latest results about the production of light (anti)nuclei in pp collisions at $$ \sqrt{s} $$ s = 13 TeV are presented, focusing on the comparison with the predictions of coalescence and therma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…It is evident that there is no single parameterisation of the system size that is able to fit both the measured B 2 and B 3 . However, as stated also in [24], charged-particle multiplicity is not a perfect proxy for the system size, because for each multiplicity the source radius depends also on the transverse-momentum of the particle of interest. Anyhow, the data corresponding to the different collision systems and energies confirm a trend with multiplicity, which can be interpreted as an effect of the interplay between the size of the system and that of the nucleus.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is evident that there is no single parameterisation of the system size that is able to fit both the measured B 2 and B 3 . However, as stated also in [24], charged-particle multiplicity is not a perfect proxy for the system size, because for each multiplicity the source radius depends also on the transverse-momentum of the particle of interest. Anyhow, the data corresponding to the different collision systems and energies confirm a trend with multiplicity, which can be interpreted as an effect of the interplay between the size of the system and that of the nucleus.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, it is now understood that the increase with transverse momentum of the coalescence parameter in INEL > 0 collisions is, in large part, due to the change in shape of the transverse momentum spectra of protons in different multiplicity intervals [10]. It is also worth mentioning that in pp collisions at high multiplicity (HM) [24], where the system size is larger than the one resulting from INEL > 0 collisions, the raise with p T cannot be neglected even in fine multiplicity classes. In [24], it was shown that the B A as a function of transverse momentum can be described by coalescence predictions, assuming a Gaussian wave function for the nuclei.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements are usually performed in pA or AA reactions [43][44][45][46][47]. Data in pp collisions are scarce and only available at TeV energies [17,48,49]. We thus do not have the chance to test our model calculation in lower collision energies below TeV.…”
Section: Antinucleus Formationmentioning
confidence: 99%